Neural inputs from spinal motor neurons to lateralis vastus muscle: Comparison between sprinters and nonathletes - Qiu, Fang; Liu, Xiaodong; Xu, Yilin; Shi, Lijun; Sheng, Xinjun; Chen, Chen (Frontiers in Physiology, 2022)
The adaptation of neural contractile properties has been observed in previous work. However, the neural changes on the motor unit (MU) level remain largely unknown. Voluntary movements are controlled through the precise activation of MU populations. In this work, we estimate the neural inputs from the spinal motor neurons to the muscles during isometric contractions and characterize the neural adaptation during training by comparing the MU properties decomposed from sprinters and nonathletes. Twenty subjects were recruited and divided into two groups. The high-density surface electromyography (EMG) signals were recorded from the lateralis vastus muscle during the isometric contraction of knee extension and were then decomposed into MU spike trains. Each MU’s action potential and discharge properties were extracted for comparison across subject groups and tasks. A total of 1097 MUs were identified from all subjects. Results showed that the discharge rates and amplitudes of MUAPs from athletes were significantly higher than those from nonathletes. These results demonstrate the impact of training on the rate coding and contractile adaptation at the MU population level, which indicates the great potential of EMG decomposition in physiological investigations.